Zoledronate and Molecular Iodine Cause Synergistic Cell Death in Triple Negative Breast Cancer through Endoplasmic Reticulum Stress. (18th May 2016) - Tripathi, Ranu; Singh, Preeti; Singh, Aru; Chagtoo, Megha; Khan, Sajid; Tiwari, Swasti; Agarwal, Gaurav; Meeran, Syed Musthapa; Godbole, Madan M
ABSTRACT: Women consuming molecular iodine (I2 ) through seaweeds suffer the least from breast cancers. Zoledronate (Zol) is in clinical use for alleviation of bone pain in cancer patients. Triple negative breast cancers exhibit high mortality due to lack of neoadjuvant chemotherapy. I2 and Zol independently cause weak antiproliferative and apoptotic effect. So far, their combined effects have not been tested. We analyzed the effect of combination of I2 with Zol as a potent adjuvant therapeutic agent for triple negative breast cancer cells (MDA-MBA-231) and in the mice model of breast cancer. Cell viability, terminal deoxynucleotidyl transferase dUTP nick end labeling staining, Western blotting, real-time PCR, flow cytometry, and other assays were performed for assessing cell death, calcium levels, and migration potential, respectively, in treated cells. The increased caspase 8, increased [Ca 2+ ]c levels, and endoplasmic reticulum (ER) stress resulted in apoptosis. Real time and fluorescence-based analysis demonstrated that the combination treatment targets ER Ca 2+ homeostasis chaperons leading to apoptosis. Combination therapy reduces metalloproteinases 2 and 9, inhibits invasion/migration of cells, and prevents growth of tumor in mice. I2 + Zol combination treatment induces synergistic increase in ER-mediated apoptosis, reduces invasion/migration potential of MDA-MB-231 cells, and exhibits antiproliferative property in vivo demonstrating its potential as combination therapy.